2021
DOI: 10.1002/jcla.24174
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterozygous HTRA1 mutation in an Asian family with CADASIL‐like disease

Abstract: Cerebral small vessel disease (CSVD) refers to lesions of the cerebral arterioles, venules, and capillaries caused by various causes. 1 Clinical manifestations of this type of disease are cognitive decline, abnormal gait, decreased executive function, mental symptoms, etc. 2 CSVD can be divided into sporadic and hereditary. Sporadic CSVD is mainly related to age, hypertension, diabetes, smoking, and other risk factors. 3 Hereditary CSVD accounts for approximately 5% of all cerebrovascular diseases caused by ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Up to this study, there have been 40 single heterozygous HTRA1 mutations ( Figure 2 ) ( Verdura et al, 2015 ; Ihara, 2016 ; Nozaki et al, 2016 ; Bougea et al, 2017 ; Di Donato et al, 2017 ; Ito et al, 2018 ; Kono et al, 2018 ; Lee et al, 2018 ; Pati and Battisti, 2018 ; Thaler et al, 2018 ; Wu et al, 2018 ; Zhang et al, 2018 ; Favaretto et al, 2019 ; Liu et al, 2020 ; Ohta et al, 2020 ; Oluwole et al, 2020 ; Zhuo et al, 2020 ; Bekircan-Kurt et al, 2021 ; Grigaitė et al, 2021 ; Shang et al, 2021 ; Cao et al, 2022 ). In this study, we collected 95 Chinese CSVD patients and performed genetic analysis in the probands.…”
Section: Discussionmentioning
confidence: 96%
“…Up to this study, there have been 40 single heterozygous HTRA1 mutations ( Figure 2 ) ( Verdura et al, 2015 ; Ihara, 2016 ; Nozaki et al, 2016 ; Bougea et al, 2017 ; Di Donato et al, 2017 ; Ito et al, 2018 ; Kono et al, 2018 ; Lee et al, 2018 ; Pati and Battisti, 2018 ; Thaler et al, 2018 ; Wu et al, 2018 ; Zhang et al, 2018 ; Favaretto et al, 2019 ; Liu et al, 2020 ; Ohta et al, 2020 ; Oluwole et al, 2020 ; Zhuo et al, 2020 ; Bekircan-Kurt et al, 2021 ; Grigaitė et al, 2021 ; Shang et al, 2021 ; Cao et al, 2022 ). In this study, we collected 95 Chinese CSVD patients and performed genetic analysis in the probands.…”
Section: Discussionmentioning
confidence: 96%
“… 33 , 39 , 40 MRI of the head showed typical features of cerebral small-vessel disease, with pathological manifestations of intimal thickening, epicardial fibrosis, degeneration and loss of smooth muscle cells, and delamination and splitting of the internal elastic lamina of small vessels. 37 There were no osmiophilic granules on the surface of vascular smooth muscle on electron microscopy. It has been shown that mutations in the heterozygous HTRA1 gene result in a reduction in the protein hydrolysis activity of HTRA1, 41 which is accompanied by an increase in the levels of TGF-β1/Smad proteins, with a similar molecular mechanism to CARASIL.…”
Section: Htra1 Gene Abnormalities and Cerebrovascular Diseasementioning
confidence: 93%
“…Cerebral autosomal-dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) can be divided into 2 types, one is CADASIL type 1 (CADASIL1, OMIM 125310), caused by mutations in the NOTCH receptor 3 gene (NOTCH3), is the most common hereditary cerebral small vessel disease 35 and is broadly referred to collectively as CADASIL, while the other type, CADASIL type 2 (CADASIL2, OMIM 616779), also known as symptomatic carriers of HTRA1 gene mutations, 33 , 36 and studies have found that HTRA1 heterozygous mutations can cause cerebrovascular abnormalities. 37 The clinical manifestations of CARASIL and symptomatic carriers of HTRA1 mutations are approximately the same, but the latter have milder clinical symptoms 14 , 38 and later onset. 33 , 39 , 40 MRI of the head showed typical features of cerebral small-vessel disease, with pathological manifestations of intimal thickening, epicardial fibrosis, degeneration and loss of smooth muscle cells, and delamination and splitting of the internal elastic lamina of small vessels.…”
Section: Htra1 Gene Abnormalities and Cerebrovascular Diseasementioning
confidence: 99%